A flame retardant TPU film and preparation method thereof
By adding functional additives such as flame retardant, toughener, antioxidant and other functional additives to the TPU film, and using modified additives and chemical resistant agents, the flame retardant, water vapor barrier and tear performance of the TPU film is optimized, which solves the problem of difficult performance coordination in the prior art, and improves the UV resistance and corrosion resistance of the product.
Patent Information
- Application Number
- CN202510031743.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-09
AI Technical Summary
When the existing TPU films improve flame retardant performance, they are prone to poor moisture barrier performance and tear performance, making it difficult to achieve coordinated improvements in flame retardant, moisture barrier and tear. At the same time, the product's ultraviolet resistance and corrosion resistance are also poor.
By adding flame retardant, toughener, antioxidant, silane coupling agent and lubricant to the TPU film as functional additives, and using modification additives and chemical resistant agents as preparation materials, the coordinated improvement of the flame retardant properties of the product, and the coordinated improvement of the moisture barrier and tear performance are optimized, while improving the UV resistance and corrosion resistance of the product.
The coordinated improvement of the flame retardant, water vapor barrier and tear performance of TPU film is achieved, and the UV resistance and corrosion resistance of the product is significantly improved, and the use efficiency is improved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of TPU films, and in particular to a flame-retardant TPU film and a preparation method thereof. Background Art
[0002] TPU film is made from TPU pellets through special processes such as calendering, casting, film blowing, and coating. TPU, or thermoplastic polyurethane elastomer, is made by extruding and mixing MDI containing NCO functional groups and polyether polyol 1.4BG containing OH functional groups. Due to its good elasticity, excellent physical properties, and good mechanical strength, TPU is a plastic material frequently used by plastic processing industries, and its products cover the range of industrial applications and civilian necessities.
[0003] In order to improve the flame retardant properties of products, existing TPU films easily lead to poor water vapor barrier and tear properties of products. It is difficult for the products to achieve coordinated improvements in flame retardancy, water vapor barrier and tearing. In addition, the products have poor UV resistance and corrosion resistance, which limits the efficiency of product use. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a flame retardant TPU film and a preparation method thereof to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a flame retardant TPU film, comprising the following raw materials in parts by weight:
[0007] TPU 45-50 parts, modifying additives 7-11 parts, chemical resistance agent 6-9 parts, flame retardant 5-8 parts, toughening agent 3-5 parts, antioxidant 2-3 parts, silane coupling agent 2-3 parts, lubricant 1-3 parts.
[0008] Preferably, the antioxidant is didodecyl alcohol ester; the flame retardant is magnesium hydroxide; the toughening agent is hydroxyethyl acrylate; the silane coupling agent is silane coupling agent KH560; and the lubricant is erucamide.
[0009] Preferably, the preparation method of the modified additive is:
[0010] S01: 2-5 parts of silane coupling agent, 2-4 parts of ethanol and 1-2 parts of water are uniformly mixed by weight at a mixing temperature of 50-55° C. and a mixing speed of 400 r / min for 1 hour to obtain a silane coupling agent liquid;
[0011] Dispersing 3-5 parts of nano-silica sol and 2-5 parts of nano-calcium carbonate into 5-8 parts of silane coupling agent liquid by weight to obtain a modified sol liquid;
[0012] S02: preheating the halloysite at 55-60° C. for 1 hour to obtain preheated halloysite; then immersing the preheated halloysite in a lanthanum chloride solution having a weight of 2-5 times the total weight of the preheated halloysite, stirring sufficiently, to obtain a halloysite agent;
[0013] The modified sol solution and the halloysite agent are subjected to ultrasonic modification treatment in a weight ratio of 5:3 to obtain a modified halloysite solution;
[0014] S03: The modified halloysite liquid and the ball milling additive are subjected to ball milling treatment in a weight ratio of (5-7):3, the ball milling speed is 750-850 r / min, the ball milling is performed for 1 hour, and after the ball milling is completed, the modified additive is filtered and dried to obtain the modified additive.
[0015] Preferably, the ultrasonic power of the ultrasonic modification treatment is 450-500W, and the ultrasonic time is 20-30min; the silane coupling agent is silane coupling agent KH550; and the mass fraction of the lanthanum chloride solution is 2-5%.
[0016] Preferably, the preparation method of the ball milling additive is:
[0017] The montmorillonite is heat treated at 155-165°C for 15-20 minutes, then heated to 260-270°C at a rate of 1-3°C / min, kept at this temperature for 10 minutes, and then air-cooled to 60°C and kept at this temperature to obtain heat-treated montmorillonite;
[0018] The heat-treated montmorillonite is placed in a sufficient amount of additive liquid and stirred. After stirring, it is filtered and dried to obtain a ball mill additive; the additive liquid includes the following raw materials in parts by weight: 2-5 parts of dopamine hydrochloride solution, 1-3 parts of polyvinyl alcohol fiber, 2-4 parts of hydroxyapatite and 1-2 parts of sodium lignin sulfonate solution.
[0019] Preferably, the stirring speed of the stirring treatment is 650-750 r / min, and the stirring is for 1-2 hours; the mass fraction of the dopamine hydrochloride solution is 2-5%; and the mass fraction of the sodium lignin sulfonate solution is 3-6%.
[0020] Preferably, the preparation method of the chemical resistance agent is:
[0021] S11: adding 2-4 parts of nano-barium sulfate, 1-3 parts of 5% by weight sodium dodecylbenzene sulfonate solution and 1-2 parts of citric acid to 5-8 parts of 2% by weight yttrium nitrate solution, stirring sufficiently to obtain a nano-barium sulfate solution;
[0022] S12: First, stir the nano-titanium dioxide evenly in a sufficient amount of hydrogen peroxide solution, then wash it with boiling water for 3 times and dry it to obtain dry nano-titanium dioxide; place the dry nano-titanium dioxide in a nano-barium sulfate solution that is 3-5 times the total weight of the nano-titanium dioxide, stir it sufficiently, then wash it with water, filter it, and dry it to obtain a chemical resistance agent.
[0023] Preferably, the mass fraction of the hydrogen peroxide solution is 5%.
[0024] The present invention also provides a method for preparing a flame retardant TPU film, comprising the following steps:
[0025] The raw materials are weighed according to weight; the raw materials are melted, extruded, cooled, and pelletized to obtain a premix; the premix is extruded and cast to obtain a flame-retardant TPU film.
[0026] Preferably, the temperature of the melt extrusion is 185°C; the screw speed of the extrusion casting is 300r / min, the extrusion temperature is 190°C, and the roller speed is 450-500m / min.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The TPU film of the present invention adopts TPU as a matrix, adds flame retardants, toughening agents, antioxidants, silane coupling agents and lubricants as functional additives, and adds modifying additives and chemical resistance agents as blending raw materials, thereby optimizing the flame retardancy of the product, the coordinated improvement of water vapor barrier and tearing, and the product has significant effects on UV resistance and corrosion resistance stability;
[0029] The modified additive uses nano-silica sol, nano-calcium carbonate and silane coupling agent liquid as the blending raw materials. At the same time, halloysite is preheated at 55-60°C for 1h, then treated with lanthanum chloride solution, and then blended with the modified sol liquid. Halloysite is used as the matrix material, and nano-calcium carbonate and other raw materials are coordinated. Through the synergistic effect between the raw materials, the ball milling additive is then combined to optimize the system. Nano-calcium carbonate and halloysite are dispersed in the system, thereby enhancing the performance effect of the product system. At the same time, the ball milling additive uses montmorillonite heat-treated at 155-165°C for 1 5-20min, then heat to 260-270℃ at a rate of 1-3℃ / min, keep warm for 10min, and then air cool to 60℃. Through the thermal improvement treatment of montmorillonite, the activity efficiency and interlamellar spacing of montmorillonite are enhanced. At the same time, the coordination between dopamine hydrochloride solution, polyvinyl alcohol fiber, hydroxyapatite and sodium lignin sulfonate solution, and the montmorillonite is coordinated with polyvinyl alcohol fiber and hydroxyapatite to reinforce the system, further optimize the system performance, thereby improving the UV resistance and corrosion resistance stability of the product;
[0030] The chemical resistance agent is made of nano-titanium dioxide treated with hydrogen peroxide solution to optimize its active efficiency, and then formulated with nano-barium sulfate solution to enhance the system performance and further coordinate the modified additives to improve the performance of the product. The nano-barium sulfate solution is made of nano-barium sulfate, 5% by mass sodium dodecylbenzene sulfonate solution and citric acid, and 2% by mass yttrium nitrate solution. Through the mutual coordination and assistance between the raw materials, the performance of the product is further improved, and the product's UV resistance and corrosion resistance stability are enhanced. DETAILED DESCRIPTION
[0031] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] A flame-retardant TPU film of this embodiment includes the following raw materials in parts by weight:
[0033] TPU 45-50 parts, modifying additives 7-11 parts, chemical resistance agent 6-9 parts, flame retardant 5-8 parts, toughening agent 3-5 parts, antioxidant 2-3 parts, silane coupling agent 2-3 parts, lubricant 1-3 parts.
[0034] The antioxidant in this embodiment is didodecyl alcohol ester; the flame retardant is magnesium hydroxide; the toughening agent is hydroxyethyl acrylate; the silane coupling agent is silane coupling agent KH560; and the lubricant is erucamide.
[0035] The preparation method of the modified additive of this embodiment is:
[0036] S01: 2-5 parts of silane coupling agent, 2-4 parts of ethanol and 1-2 parts of water are uniformly mixed by weight at a mixing temperature of 50-55° C. and a mixing speed of 400 r / min for 1 hour to obtain a silane coupling agent liquid;
[0037] Dispersing 3-5 parts of nano-silica sol and 2-5 parts of nano-calcium carbonate into 5-8 parts of silane coupling agent liquid by weight to obtain a modified sol liquid;
[0038] S02: preheating the halloysite at 55-60° C. for 1 hour to obtain preheated halloysite; then immersing the preheated halloysite in a lanthanum chloride solution having a weight of 2-5 times the total weight of the preheated halloysite, stirring sufficiently, to obtain a halloysite agent;
[0039] The modified sol solution and the halloysite agent are subjected to ultrasonic modification treatment in a weight ratio of 5:3 to obtain a modified halloysite solution;
[0040] S03: The modified halloysite liquid and the ball milling additive are subjected to ball milling treatment in a weight ratio of (5-7):3, the ball milling speed is 750-850r / min, the ball milling is performed for 1h, and after the ball milling is completed, the modified additive is filtered and dried to obtain the modified additive.
[0041] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 450-500W, and the ultrasonic time is 20-30min; the silane coupling agent is silane coupling agent KH550; and the mass fraction of the lanthanum chloride solution is 2-5%.
[0042] The preparation method of the ball milling additive of this embodiment is:
[0043] The montmorillonite is heat treated at 155-165°C for 15-20 minutes, then heated to 260-270°C at a rate of 1-3°C / min, kept at this temperature for 10 minutes, and then air-cooled to 60°C and kept at this temperature to obtain heat-treated montmorillonite;
[0044] The heat-treated montmorillonite is placed in a sufficient amount of additive liquid and stirred. After stirring, it is filtered and dried to obtain a ball mill additive; the additive liquid includes the following raw materials in parts by weight: 2-5 parts of dopamine hydrochloride solution, 1-3 parts of polyvinyl alcohol fiber, 2-4 parts of hydroxyapatite and 1-2 parts of sodium lignin sulfonate solution.
[0045] The stirring speed of the stirring treatment in this embodiment is 650-750 r / min, and the stirring is for 1-2 hours; the mass fraction of the dopamine hydrochloride solution is 2-5%; and the mass fraction of the sodium lignin sulfonate solution is 3-6%.
[0046] The preparation method of the chemical resistance agent of this embodiment is:
[0047] S11: adding 2-4 parts of nano-barium sulfate, 1-3 parts of 5% by weight sodium dodecylbenzene sulfonate solution and 1-2 parts of citric acid to 5-8 parts of 2% by weight yttrium nitrate solution, stirring sufficiently to obtain a nano-barium sulfate solution;
[0048] S12: First, stir the nano-titanium dioxide evenly in a sufficient amount of hydrogen peroxide solution, then wash it with boiling water for 3 times and dry it to obtain dry nano-titanium dioxide; place the dry nano-titanium dioxide in a nano-barium sulfate solution that is 3-5 times the total weight of the nano-titanium dioxide, stir it sufficiently, then wash it with water, filter it, and dry it to obtain a chemical resistance agent.
[0049] The mass fraction of the hydrogen peroxide solution in this embodiment is 5%.
[0050] A method for preparing a flame-retardant TPU film in this embodiment comprises the following steps:
[0051] The raw materials are weighed according to weight; the raw materials are melted, extruded, cooled, and pelletized to obtain a premix; the premix is extruded and cast to obtain a flame-retardant TPU film.
[0052] The temperature of the melt extrusion in this embodiment is 185°C; the screw speed of the extrusion casting is 300r / min, the extrusion temperature is 190°C, and the roller speed is 450-500m / min.
[0053] Embodiment 1: A flame retardant TPU film, comprising the following raw materials in parts by weight:
[0054] TPU 45 parts, modifying additives 7 parts, chemical resistance agent 6 parts, flame retardant 5 parts, toughening agent 3 parts, antioxidant 2 parts, silane coupling agent 2 parts, lubricant 1 part.
[0055] The antioxidant in this embodiment is didodecyl alcohol ester; the flame retardant is magnesium hydroxide; the toughening agent is hydroxyethyl acrylate; the silane coupling agent is silane coupling agent KH560; and the lubricant is erucamide.
[0056] The preparation method of the modified additive of this embodiment is:
[0057] S01: 2 parts of silane coupling agent, 2 parts of ethanol and 1 part of water were uniformly mixed by weight at a mixing temperature of 50° C. and a mixing speed of 400 r / min for 1 h to obtain a silane coupling agent liquid;
[0058] Dispersing 3 parts of nano-silica sol and 2 parts of nano-calcium carbonate into 5 parts of silane coupling agent liquid by weight to obtain a modified sol liquid;
[0059] S02: preheating the halloysite at 55° C. for 1 h to obtain preheated halloysite; then immersing the preheated halloysite in a lanthanum chloride solution having an amount twice the total weight of the preheated halloysite, stirring sufficiently, to obtain a halloysite agent;
[0060] The modified sol solution and the halloysite agent are subjected to ultrasonic modification treatment in a weight ratio of 5:3 to obtain a modified halloysite solution;
[0061] S03: The modified halloysite liquid and the ball milling additive are subjected to ball milling improvement treatment at a weight ratio of 5:3, the ball milling speed is 750 r / min, the ball milling is performed for 1 hour, and after the ball milling is completed, the modified additive is filtered and dried to obtain the modified additive.
[0062] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 450W, and the ultrasonic time is 20min; the silane coupling agent is silane coupling agent KH550; and the mass fraction of the lanthanum chloride solution is 2%.
[0063] The preparation method of the ball milling additive of this embodiment is:
[0064] The montmorillonite was heat treated at 155°C for 15 minutes, then heated to 260°C at a rate of 1°C / min, kept at that temperature for 10 minutes, and then air-cooled to 60°C and kept at that temperature to obtain heat-treated montmorillonite.
[0065] The heat-treated montmorillonite is placed in a sufficient amount of additive liquid and stirred. After stirring, it is filtered and dried to obtain a ball mill additive; the additive liquid includes the following raw materials in parts by weight: 2 parts of dopamine hydrochloride solution, 1 part of polyvinyl alcohol fiber, 2 parts of hydroxyapatite and 1 part of sodium lignin sulfonate solution.
[0066] The stirring speed of the stirring treatment in this embodiment is 650 r / min, and the stirring is for 1 hour; the mass fraction of the dopamine hydrochloride solution is 2%; and the mass fraction of the sodium lignin sulfonate solution is 3%.
[0067] The preparation method of the chemical resistance agent of this embodiment is:
[0068] S11: adding 2 parts by weight of nano-barium sulfate, 1 part by weight of 5% sodium dodecylbenzene sulfonate solution and 1 part by weight of citric acid to 5 parts by weight of 2% yttrium nitrate solution, stirring sufficiently to obtain a nano-barium sulfate solution;
[0069] S12: First, stir the nano-titanium dioxide evenly in a sufficient amount of hydrogen peroxide solution, then wash it with boiling water for 3 times and dry it to obtain dry nano-titanium dioxide; place the dry nano-titanium dioxide in a nano-barium sulfate solution with a weight that is 3 times the total weight of the nano-titanium dioxide, stir it sufficiently, then wash it with water, filter it and dry it to obtain a chemical resistance agent.
[0070] The mass fraction of the hydrogen peroxide solution in this embodiment is 5%.
[0071] A method for preparing a flame-retardant TPU film in this embodiment comprises the following steps:
[0072] The raw materials are weighed according to weight; the raw materials are melted, extruded, cooled, and pelletized to obtain a premix; the premix is extruded and cast to obtain a flame-retardant TPU film.
[0073] The temperature of the melt extrusion in this embodiment is 185°C; the screw speed of the extrusion casting is 300r / min, the extrusion temperature is 190°C, and the roller speed is 450m / min.
[0074] Embodiment 2: A flame retardant TPU film, comprising the following raw materials in parts by weight:
[0075] 50 parts of TPU, 11 parts of modifying additives, 9 parts of chemical resistance agent, 8 parts of flame retardant, 5 parts of toughening agent, 3 parts of antioxidant, 3 parts of silane coupling agent, and 3 parts of lubricant.
[0076] The antioxidant in this embodiment is didodecyl alcohol ester; the flame retardant is magnesium hydroxide; the toughening agent is hydroxyethyl acrylate; the silane coupling agent is silane coupling agent KH560; and the lubricant is erucamide.
[0077] The preparation method of the modified additive of this embodiment is:
[0078] S01: 5 parts of silane coupling agent, 4 parts of ethanol and 2 parts of water were uniformly mixed by weight at a mixing temperature of 55° C. and a mixing speed of 400 r / min for 1 h to obtain a silane coupling agent liquid;
[0079] Dispersing 5 parts of nano-silica sol and 5 parts of nano-calcium carbonate into 8 parts of silane coupling agent liquid by weight to obtain a modified sol liquid;
[0080] S02: preheating the halloysite at 60° C. for 1 h to obtain preheated halloysite; then immersing the preheated halloysite in a lanthanum chloride solution having a weight that is 5 times the total weight of the preheated halloysite, stirring sufficiently, to obtain a halloysite agent;
[0081] The modified sol solution and the halloysite agent are subjected to ultrasonic modification treatment in a weight ratio of 5:3 to obtain a modified halloysite solution;
[0082] S03: The modified halloysite liquid and the ball milling additive are subjected to ball milling improvement treatment at a weight ratio of 7:3, the ball milling speed is 850 r / min, the ball milling is performed for 1 hour, and after the ball milling is completed, the modified additive is filtered and dried to obtain the modified additive.
[0083] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 500 W, and the ultrasonic time is 30 min; the silane coupling agent is silane coupling agent KH550; and the mass fraction of the lanthanum chloride solution is 5%.
[0084] The preparation method of the ball milling additive of this embodiment is:
[0085] The montmorillonite was heat treated at 165°C for 20 minutes, then heated to 270°C at a rate of 3°C / min, kept at this temperature for 10 minutes, and then air-cooled to 60°C and kept at this temperature to obtain heat-treated montmorillonite.
[0086] The heat-treated montmorillonite is placed in a sufficient amount of additive liquid and stirred. After stirring, it is filtered and dried to obtain a ball mill additive; the additive liquid includes the following raw materials in parts by weight: 5 parts of dopamine hydrochloride solution, 3 parts of polyvinyl alcohol fiber, 4 parts of hydroxyapatite and 2 parts of sodium lignin sulfonate solution.
[0087] The stirring speed of the stirring treatment in this embodiment is 750 r / min, and the stirring is for 2 hours; the mass fraction of the dopamine hydrochloride solution is 5%; and the mass fraction of the sodium lignin sulfonate solution is 6%.
[0088] The preparation method of the chemical resistance agent of this embodiment is:
[0089] S11: adding 4 parts of nano-barium sulfate, 3 parts of 5% sodium dodecylbenzene sulfonate solution and 2 parts of citric acid to 8 parts of 2% yttrium nitrate solution by weight, stirring sufficiently to obtain a nano-barium sulfate solution;
[0090] S12: First, stir the nano-titanium dioxide evenly in a sufficient amount of hydrogen peroxide solution, then wash it with boiling water for 3 times and dry it to obtain dry nano-titanium dioxide; place the dry nano-titanium dioxide in a nano-barium sulfate solution that is 5 times the total weight of the nano-titanium dioxide and stir it sufficiently, then wash it with water, filter it and dry it to obtain a chemical resistance agent.
[0091] The mass fraction of the hydrogen peroxide solution in this embodiment is 5%.
[0092] A method for preparing a flame-retardant TPU film in this embodiment comprises the following steps:
[0093] The raw materials are weighed according to weight; the raw materials are melted, extruded, cooled, and pelletized to obtain a premix; the premix is extruded and cast to obtain a flame-retardant TPU film.
[0094] The temperature of the melt extrusion in this embodiment is 185°C; the screw speed of the extrusion casting is 300r / min, the extrusion temperature is 190°C, and the roller speed is 450-500m / min.
[0095] Embodiment 3: A flame retardant TPU film, comprising the following raw materials in parts by weight:
[0096] TPU 47.5 parts, modifying additive 9 parts, chemical resistance agent 7.5 parts, flame retardant 6.5 parts, toughening agent 4 parts, antioxidant 2.5 parts, silane coupling agent 2.5 parts, lubricant 2 parts.
[0097] The antioxidant in this embodiment is didodecyl alcohol ester; the flame retardant is magnesium hydroxide; the toughening agent is hydroxyethyl acrylate; the silane coupling agent is silane coupling agent KH560; and the lubricant is erucamide.
[0098] The preparation method of the modified additive of this embodiment is:
[0099] S01: 3.5 parts of silane coupling agent, 3 parts of ethanol and 1.5 parts of water were uniformly mixed by weight at a mixing temperature of 52.5° C. and a mixing speed of 400 r / min for 1 h to obtain a silane coupling agent liquid;
[0100] Dispersing 4 parts of nano-silica sol and 3.5 parts of nano-calcium carbonate into 6.5 parts of silane coupling agent liquid by weight to obtain a modified sol liquid;
[0101] S02: preheating the halloysite at 57.5° C. for 1 h to obtain preheated halloysite; then immersing the preheated halloysite in a lanthanum chloride solution having a weight that is 3.5 times the total weight of the preheated halloysite, stirring sufficiently, to obtain a halloysite agent;
[0102] The modified sol solution and the halloysite agent are subjected to ultrasonic modification treatment in a weight ratio of 5:3 to obtain a modified halloysite solution;
[0103] S03: The modified halloysite liquid and the ball milling additive are subjected to ball milling improvement treatment at a weight ratio of 2:1, the ball milling speed is 800 r / min, the ball milling is performed for 1 hour, and after the ball milling is completed, the modified additive is filtered and dried to obtain the modified additive.
[0104] The ultrasonic power of the ultrasonic modification treatment in this embodiment is 475W, and the ultrasonic time is 25min; the silane coupling agent is silane coupling agent KH550; and the mass fraction of the lanthanum chloride solution is 3.5%.
[0105] The preparation method of the ball milling additive of this embodiment is:
[0106] The montmorillonite was heat treated at 160°C for 17.5 min, then heated to 265°C at a rate of 2°C / min, kept at that temperature for 10 min, and then air-cooled to 60°C and kept at that temperature to obtain heat-treated montmorillonite.
[0107] The heat-treated montmorillonite is placed in a sufficient amount of additive liquid and stirred. After stirring, it is filtered and dried to obtain a ball mill additive; the additive liquid includes the following raw materials in parts by weight: 3.5 parts of dopamine hydrochloride solution, 2 parts of polyvinyl alcohol fiber, 3 parts of hydroxyapatite and 1.5 parts of sodium lignin sulfonate solution.
[0108] The stirring speed of the stirring treatment in this embodiment is 700 r / min, and the stirring is for 1.5 h; the mass fraction of the dopamine hydrochloride solution is 3.5%; and the mass fraction of the sodium lignin sulfonate solution is 4.5%.
[0109] The preparation method of the chemical resistance agent of this embodiment is:
[0110] S11: adding 3 parts of nano-barium sulfate, 2 parts of 5% sodium dodecylbenzene sulfonate solution and 1.5 parts of citric acid to 6.5 parts of 2% yttrium nitrate solution by weight, stirring well, to obtain nano-barium sulfate solution;
[0111] S12: First, stir the nano-titanium dioxide evenly in a sufficient amount of hydrogen peroxide solution, then wash it with boiling water for 3 times and dry it to obtain dry nano-titanium dioxide; place the dry nano-titanium dioxide in a nano-barium sulfate solution with a weight that is 4 times the total weight of the nano-titanium dioxide, stir it sufficiently, then wash it with water, filter it with suction, and dry it to obtain a chemical resistance agent.
[0112] The mass fraction of the hydrogen peroxide solution in this embodiment is 5%.
[0113] A method for preparing a flame-retardant TPU film in this embodiment comprises the following steps:
[0114] The raw materials are weighed according to weight; the raw materials are melted, extruded, cooled, and pelletized to obtain a premix; the premix is extruded and cast to obtain a flame-retardant TPU film.
[0115] The temperature of the melt extrusion in this embodiment is 185°C; the screw speed of the extrusion casting is 300r / min, the extrusion temperature is 190°C, and the roller speed is 470m / min.
[0116] Comparative Example 1:
[0117] The difference from Example 3 is that no modifying additive is added to the TPU film.
[0118] Comparative Example 2:
[0119] The difference from Example 3 is that in the preparation of the modified additive, no modified halloysite liquid is added in the process of step S03.
[0120] Comparative Example 3:
[0121] The difference from Example 3 is that in the process of step S02, no halloysite agent is added in the preparation of the modified halloysite liquid.
[0122] Comparative Example 4:
[0123] The difference from Example 3 is that the halloysite agent is directly replaced by the halloysite raw material without being preheated or immersed in the lanthanum chloride solution for treatment.
[0124] Comparative Example 5:
[0125] The difference from Example 3 is that no modified sol solution is added to the modified halloysite solution.
[0126] Comparative Example 6:
[0127] The difference from Example 3 is that no nano-silica sol and nano-calcium carbonate are added in the preparation of the modified sol solution.
[0128] Comparative Example 7:
[0129] The difference from Example 3 is that no ball milling additive is added in the preparation of the modified additive.
[0130] Comparative Example 8:
[0131] The difference from Example 3 is that no chemical resistance agent is added to the TPU film.
[0132] Comparative Example 9:
[0133] The difference from Example 3 is that no nano barium sulfate solution is added to the chemical resistance agent for treatment.
[0134] Comparative Example 10:
[0135] The difference from Example 3 is that no nano-barium sulfate and citric acid are added to the nano-barium sulfate solution.
[0136] Comparative Example 11:
[0137] The difference from Example 3 is that no dry nano-titanium dioxide is added to the chemical resistance agent. The specific operation method is: 3 parts of nano-barium sulfate, 2 parts of 5% by mass sodium dodecylbenzene sulfonate solution and 1.5 parts of citric acid are added to 6.5 parts of 2% by mass yttrium nitrate solution, stirred thoroughly, and then filtered and dried to obtain the chemical resistance agent.
[0138] The products of Examples 1-3 and Comparative Examples 1-11 were subjected to flame retardancy, water vapor barrier and tearing performance tests, as well as product UV resistance and corrosion resistance stability tests (the products were placed in a 5% by mass hydrochloric acid mist and a UV irradiation energy of 3000MJ / m 2 , processed for 48h), the performance measurement results are shown in Table 1.
[0139] Table 1 Product performance test results of Examples 1-3 and Comparative Examples 1-11:
[0140] It can be concluded from Examples 1-3 and Comparative Examples 1-11 that the limiting oxygen index, tear resistance and water vapor transmittance of Example 3 of the present invention can achieve coordinated improvements;
[0141] It can be seen from Comparative Example 1, Comparative Example 8 and Example 3 that when neither the modifying additive nor the chemical resistance agent is added to the TPU film, the product performance deteriorates significantly. Only when the two are coordinated and work together, the product performance effect is most significant.
[0142] It can be seen from Comparative Examples 1-7 and Example 3 that in the preparation of the modified additive, the modified halloysite liquid was not added in the process of step S03, the halloysite agent was not added in the preparation of the modified halloysite liquid, the halloysite agent was directly replaced by the halloysite raw material, the modified sol liquid was not added to the modified halloysite liquid, the nano-silica sol and nano-calcium carbonate were not added in the preparation of the modified sol liquid, and the ball milling additive was not added in the preparation of the modified additive. The performance of the product has a trend of deterioration to varying degrees, especially without adding the ball milling additive. The performance of the product deteriorates more significantly. At the same time, the modified sol liquid obtained by the specific method of the present invention is combined with the modified halloysite liquid obtained by the halloysite agent and the specific ball milling additive. The performance effect of the product is the most significant, and the use of other methods instead is not as obvious as the effect of the present invention;
[0143] The performance of the products showed a trend of deterioration to varying degrees when the chemical resistance agent was not treated with nano-barium sulfate solution, nano-barium sulfate and citric acid were not added to the nano-barium sulfate solution, and dry nano-titanium dioxide was not added to the chemical resistance agent. The chemical resistance agent obtained by treating with the specific nano-barium sulfate solution of the present invention and combining with dry nano-titanium dioxide had the most significant product performance effect.
[0144] Based on the fact that ball milling additives have a significant impact on product performance, the present invention further explores the impact of ball milling additives on product performance.
[0145] Experimental Example 1:
[0146] The same as Example 3, except that no heat-treated montmorillonite was added to the ball milling additive.
[0147] Experimental Example 2:
[0148] The same as Example 3, the only difference is that no additive liquid treatment is used in the preparation of the ball mill additive.
[0149] Experimental Example 3:
[0150] The same as Example 3, the only difference is that no polyvinyl alcohol fiber is added to the additive liquid.
[0151] Experimental Example 4:
[0152] The same as Example 3, except that hydroxyapatite is not added to the additive solution.
[0153] Experimental Example 5:
[0154] The same as Example 3, the only difference is that no dopamine hydrochloride solution is added to the additive liquid.
[0155] Experimental Example 6:
[0156] The same as Example 3, the only difference is that the sodium lignin sulfonate solution is not added to the additive liquid.
[0157] The products of Experimental Examples 1-6 were subjected to flame retardancy, water vapor barrier and tearing performance tests, as well as product UV resistance and corrosion resistance stability tests (the products were placed in 5% hydrochloric acid mist and UV irradiation energy of 3000MJ / m 2 , processed for 48h), the performance measurement results are shown in Table 2.
[0158] Table 2 Product performance test results of Experimental Examples 1-6:
[0159] It can be seen from Experimental Examples 1-6 that the ball milling additive does not contain heat-treated montmorillonite and does not use additive liquid treatment. Among the preparation factors of the ball milling additive, the product performance deteriorates most significantly. At the same time, the additive liquid does not contain polyvinyl alcohol fiber, hydroxyapatite, dopamine hydrochloride solution, and sodium lignin sulfonate solution. The product performance has a tendency to deteriorate to varying degrees. The ball milling additive obtained by combining the additive liquid obtained by the specific method of the present invention with the heat-treated montmorillonite has the most significant product performance effect. In the preparation of the additive liquid, the raw materials are indispensable. Only the specific raw material ratio of the present invention is used. Using other raw material ratios is not as significant as the effect of the present invention.
[0160] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0161] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A flame retardant TPU film, characterized in that: It includes the following raw materials in parts by weight: TPU 45-50 parts, modifying additives 7-11 parts, chemical resistance agent 6-9 parts, flame retardant 5-8 parts, toughening agent 3-5 parts, antioxidant 2-3 parts, silane coupling agent KH5602-3 parts, lubricant 1-3 parts; The preparation method of the modified additive is: S01: 2-5 parts of silane coupling agent KH550, 2-4 parts of ethanol and 1-2 parts of water are uniformly mixed by weight at a mixing temperature of 50-55° C. and a mixing speed of 400 r / min for 1 hour to obtain a silane coupling agent liquid; Dispersing 3-5 parts of nano-silica sol and 2-5 parts of nano-calcium carbonate into 5-8 parts of silane coupling agent liquid by weight to obtain a modified sol liquid; S02: preheating the halloysite at 55-60° C. for 1 hour to obtain preheated halloysite; then immersing the preheated halloysite in a lanthanum chloride solution having a weight of 2-5 times the total weight of the preheated halloysite, stirring sufficiently, to obtain a halloysite agent; The modified sol solution and the halloysite agent are subjected to ultrasonic modification treatment in a weight ratio of 5:3 to obtain a modified halloysite solution; S03: ball-milling the modified halloysite liquid and the ball-milling additive according to a weight ratio of (5-7):3, with a ball-milling speed of 750-850 r / min for 1 h. After the ball-milling is completed, the modified additive is filtered and dried to obtain the modified additive; The preparation method of the ball milling additive is: The montmorillonite is heat treated at 155-165°C for 15-20 minutes, then heated to 260-270°C at a rate of 1-3°C / min, kept at this temperature for 10 minutes, and then air-cooled to 60°C and kept at this temperature to obtain heat-treated montmorillonite; The heat-treated montmorillonite is placed in a sufficient amount of additive liquid and stirred, and after stirring, filtered and dried to obtain a ball milling additive; wherein the additive liquid comprises the following raw materials in parts by weight: 2-5 parts of dopamine hydrochloride solution, 1-3 parts of polyvinyl alcohol fiber, 2-4 parts of hydroxyapatite and 1-2 parts of sodium lignin sulfonate solution; The preparation method of the chemical resistance agent is: S11: adding 2-4 parts of nano-barium sulfate, 1-3 parts of 5% by weight sodium dodecylbenzene sulfonate solution and 1-2 parts of citric acid to 5-8 parts of 2% by weight yttrium nitrate solution, stirring sufficiently to obtain a nano-barium sulfate solution; S12: First, stir the nano-titanium dioxide evenly in a sufficient amount of hydrogen peroxide solution, then wash it with boiling water for 3 times and dry it to obtain dry nano-titanium dioxide; place the dry nano-titanium dioxide in a nano-barium sulfate solution that is 3-5 times the total weight of the nano-titanium dioxide, stir it sufficiently, then wash it with water, filter it, and dry it to obtain a chemical resistance agent.
2. A flame retardant TPU film according to claim 1, characterized in that: The antioxidant is didodecyl alcohol ester; the flame retardant is magnesium hydroxide; the toughening agent is hydroxyethyl acrylate; and the lubricant is erucamide.
3. The flame-retardant TPU film according to claim 1, characterized in that: The ultrasonic power of the ultrasonic modification treatment is 450-500W, and the ultrasonic time is 20-30min.
4. The flame-retardant TPU film according to claim 1, characterized in that: The mass fraction of the lanthanum chloride solution is 2-5%.
5. The flame-retardant TPU film according to claim 1, characterized in that: The stirring speed of the stirring treatment is 650-750 r / min, and the stirring is performed for 1-2 hours.
6. The flame-retardant TPU film according to claim 1, characterized in that: The mass fraction of the dopamine hydrochloride solution is 2-5%.
7. The flame-retardant TPU film according to claim 1, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 3-6%.
8. The flame-retardant TPU film according to claim 1, characterized in that: The mass fraction of the hydrogen peroxide solution is 5%.
9. A method for preparing a flame-retardant TPU film, for preparing the flame-retardant TPU film according to any one of claims 1 to 8, characterized in that: The following steps are involved: The raw materials are weighed according to weight; the raw materials are melted, extruded, cooled, and pelletized to obtain a premix; the premix is extruded and cast to obtain a flame-retardant TPU film.
10. The method for preparing a flame-retardant TPU film according to claim 9, characterized in that: The temperature of the melt extrusion is 185°C; the screw speed of the extrusion casting is 300r / min, the extrusion temperature is 190°C, and the roller speed is 450-500m / min.
Citation Information
Patent Citations
Rare-earth-modified-montmorillonite-added modified PVC (polyvinyl chloride) microporous insulation binder
CN105950052A
Preparation method of aging-resistant flame-retardant polypropylene engineering plastic
CN106280007A